Africa Diary: 1 December 2025 to 28 February 2026 - New Agenda Editorial Collective (New Agenda: SA Journal of Social and Economic Policy, 2026)
A selection of events about, and from across, Africa that are significant or interesting, or both. Compiled by the New Agenda Editorial Collective at the Institute for African Alternatives.